Physical activity assessment in coronary heart disease patients: questionnaire ODA-23+ - V. B. Krasnitskyi; D. M. Aronov; S. O. Dzhankhotov (Кардиоваскулярная терапия и профилактика, 1970)
To assess the dynamics of physical activity (PA) in patients with coronary heart disease (CHD) during rehabilitation or secondary prevention, a specialised questionnaire ODA23+ was developed. This instrument takes into account the specifics of Russian patients’ lifestyle and mentality, assesses PA levels, and evaluates PA dynamics over time. The mathematical model was created, based on experts’ opinions. After statistical analysis of the data obtained from experts, point-based weights for each answer to all 23 questions were determined. The questionnaire ODA23+ was assessed in two clinical studies of rehabilitation and secondary prevention among CHD patients after acute coronary incidents, coronary artery bypass graft surgery, or coronary endovascular intervention. It was demonstrated that the questionnaire is valid and sensitive in the dynamic assessment of PA. The questionnaire also provides an opportunity to compare the long-term effectiveness of different physical training or educational programs in CHD patients.